Trends in Inequality in Cigarette Smoking Prevalence by Income According to Recent Anti-smoking Policies in Korea: Use of Three National Surveys - Youngs Chang; Sanghyun Cho; Ikhan Kim; Jinwook Bahk; Young-Ho Khang (Korean Society for Preventive Medicine, 2018)
Objectives This study examined trends in inequality in cigarette smoking prevalence by income according to recent anti-smoking policies in Korea. Methods The data used in this study were drawn from three nationally representative surveys, the Korea National Health and Nutrition Examination Survey, the Korea Community Health Survey, and the Social Survey of Statistics Korea. We calculated the age-standardized smoking prevalence, the slope index of inequality, and the relative index of inequality by income level as a socioeconomic position indicator. Results Smoking prevalence among men decreased during the study period, but the downward trend became especially pronounced in 2015, when the tobacco price was substantially increased. Inequalities in cigarette smoking by income were evident in both genders over the study period in all three national surveys examined. Absolute inequality tended to decrease between 2014 and 2015 among men. Absolute and relative inequality by income decreased between 2008 and 2016 in women aged 30-59, except between 2014 and 2015. Conclusions The recent anti-smoking policies in Korea resulted in a downward trend in smoking prevalence among men, but not in relative inequality, throughout the study period. Absolute inequality decreased over the study period among men aged 30-59. A more aggressive tax policy is warranted to further reduce socioeconomic inequalities in smoking in young adults in Korea.